Avaliação de componentes da fibra como marcadores internos e de alcanos para estimar o fluxo de digesta no duodeno de bovinos - Mesquita, Francisco Rondon (2012)
The use of ADF as internal Marker of duodenal digesta flow was evaluated, for this the intestinal degradability of fiber was studied. Four Holstein calves (156± 33 kg), fitted with duodenal cannula T simple, and one calve fitted on the rumen, fed diet base with black oat and supplement, was used. Seven feeds were weighted on the polyester bags (7x5,5cm; 25μm) and treated at different ruminal incubation times (12, 24, 36 and 48 hours). After the respective incubations times, the bags were introduced in the duodenum of animals, recovered on the faeces and analyzed. The means of fiber fraction obtained posruminally and on the samples recovered on the faeces, were significantly different (P<0,05). The percent difference was 6,44, 2,07 e 0,90% on DM basis, for NDF, ADF and ADL, respectively. The disappearance of ADL indicated loss of particles through the pores of the bags, thereby the means were corrected for the loss of ADL, improving the regression coefficients and intercept of the regression equations, demonstrating the potential of using the ADF as an internal marker of digesta flow in ruminants. Additionally, was evaluated the duodenal digesta flow on cattle, with different markers. The means obtained from the ADF and ADL were similar, 2,025 and 2,135 kgDM/day, respectively. The n-alkanes presented low fecal recovery (C31= 63,3%; C32=46,7% e C33=75,6%), this may have contributed to the high variability of the results obtained from the n-alkanes. The n-alkane C32 overestimated the duodenal flow of DM, 3,855 kgDM/day. The ADF was useful for to measure the duodenal digesta flow, even small loss was detected, this did not prejudice the assessment. The ADF was efficient for measure digesta flow of DM, differently of the n-alkanes that overestimated (C32) and presented high variability (C31, C32 and C33).